2023
DOI: 10.1021/acs.langmuir.3c03221
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensing Properties of Pd-Decorated GeSe Monolayer toward Formaldehyde and Benzene Molecules: A First-Principles Study

Gang Guo,
Jiewen Min,
Yajuan Xu
et al.

Abstract: In this study, the gas sensing properties of formaldehyde (HCHO) and benzene (C 6 H 6 ) adsorbed on two-dimensional (2D) pristine GeSe and Pd-decorated GeSe (Pd−GeSe) monolayers are studied by using firstprinciples calculations. The adsorption energies, electronic properties, optical properties, sensitivity, and recovery time of the gas adsorption systems have been thoroughly investigated. It is found that the adsorption of C 6 H 6 on two substrate surfaces and the adsorption of HCHO on pristine GeSe are examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…These findings seem to align with previous research on the NO 2 molecule that has been published in the literature. 14 Additionally, previous investigations 22,27,65 have observed that comparing the expected partial density of states (PDOS) of a system pre- and post-adsorption could provide insight into the nature of the adsorption. The figure illustrates a modification in the PDOS distribution of the system subsequent to the adsorption of the NO 2 gas molecule onto the B 2 STe material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings seem to align with previous research on the NO 2 molecule that has been published in the literature. 14 Additionally, previous investigations 22,27,65 have observed that comparing the expected partial density of states (PDOS) of a system pre- and post-adsorption could provide insight into the nature of the adsorption. The figure illustrates a modification in the PDOS distribution of the system subsequent to the adsorption of the NO 2 gas molecule onto the B 2 STe material.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the selective detection of these three molecules can be accomplished by leveraging the varying magnitudes of conductivity changes. 65…”
Section: Resultsmentioning
confidence: 99%
“…Doping is a widely recognized method for improving the physical characteristics of 2D materials . Pd, an exceptionally active metal dopant, is extensively employed to enhance the gas sensing capabilities of doped modified 2D materials. , Considering the exceptional catalytic performance of a Pd dopant, the potential of Pd-adsorbed SiN 3 (Pd-SiN 3 ) as a chemical gas scavenger for SF 6 decomposition components was investigated in this study. Specifically, first-principles calculations were used to thoroughly investigate the interaction of a Pd-SiN 3 monolayer with four typical SF 6 decomposition gases (H 2 S, SO 2 , SOF 2 , and SO 2 F 2 ) and the corresponding geometric, electronic, optical, sensing, and desorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is partially decomposed by high-voltage arcs, causing its decomposition products to be highly corrosive and toxic with electrical equipment severely affected. Therefore, the addition of more active centers allows the BPN to act as a sensor to detect these gases to ensure proper operation of the device. Since the transition metal atom (TMA) has unfilled d valence orbitals with relatively active valence electrons, it is easy to electronically hybridize with gas molecules, while the properties can be improved with less doping or adsorption. In the case of Ru/Ti-modified stanene monolayer, for example, small molecules are adsorbed due to Ru/Ti activation of their surfaces, resulting in large adsorption energies compared to the original primary structure . The Pt-doped HfSe 2 monolayer adsorbs SO 2 and SOF 2 with more charge transfer with chemisorption .…”
Section: Introductionmentioning
confidence: 99%